Research meetings 1990-1991 - Skjenneberg (ed.), Sven (Rangifer, 1990)
Announcements of 6th Nordic Reindeer Scientists Meeting in Tromsø, Norway, Oct. 1990 and 3rd Int. Muskox Symosium in Nuuk, Greenland, Sept. 1991.